Elaboração e validação de um plano de avaliação para alunos com autismo - Ferreira, Elisangela Soares (2018)
The evaluation process of students with autism since 2008 presents a challenge for special education teachers. In the sphere of Specialized Educational Assistance (AEE) this fact is also evident and symbolizes a permanent concern. In this sense, some studies describe it as occupying a fundamental and essential role in the pedagogical process, since it is from the evaluation that it is possible to elaborate a specific action plan for these students and to follow the learning process. The evaluation process is fundamental for teachers, since it constitutes a central parameter of the potentialities and difficulties of the students, being essential to the construction of pedagogical proposals. Thus, both ESA teachers and students with autism can benefit from an evaluation tool, specifically developed to address the heterogeneity of the syndrome. Thus, this study aimed to describe the steps of the elaboration of an Assessment Plan for Students with Autism (PAAA) enrolled between the 1st and 3rd years of Elementary School. For this, the method of instrument elaboration was used and obeyed the methodology described by Kline (1995) organized in six stages: the first one consisted in the revision of the theoretical references pertinent to the subject; in the second stage, the areas, items and sub-items that deserved attention in the evaluation process were defined, and then the evaluation questions were formulated; in the third stage, 25 specialized educational attendance plans (PAEE) were collected from students with autism, prepared by teachers working in ESL rooms for content analysis; in the fourth stage a brief review of the PAAA was carried out in view of the previous results; in the fifth stage the focus group methodology was applied together with specialist teachers; in the sixth stage the final version of the PAAA was generated, having as parameters all the previous stages. At the conclusion of the generation of the final PAAA. The literature items that integrated the preliminary plan showed adequate indicators of denotative and connotative equivalence after the comparison with the EEEE of the ESA teachers. This allowed for the revision of areas, items, subitems and questions pertinent to the characteristics of the student and autism environment that were considered by teachers as potential barriers to school participation and learning. The focus group allowed adjustments of terminologies, number of questions and specificities of each area contemplated. The final version integrated the adjustments considered important in previous stages, such as colloquial vocabulary and terms appropriate to the area of education. We suggest new studies that replicate the methodology used here in other Brazilian regions, composing representative samples for education at the national level.